2023
DOI: 10.1002/oby.23668
|View full text |Cite
|
Sign up to set email alerts
|

Establishing causal relationships between sleep and adiposity traits using Mendelian randomization

Abstract: Objective: The aim of this study was to systematically evaluate the direction of any potential causal effect between sleep and adiposity traits. Methods: Two-sample Mendelian randomization was used to assess the association of genetically predicted sleep traits with adiposity and vice versa. Using data from UK Biobank and 23andMe, the sleep traits explored were morning preference (chronotype; N = 697,828), insomnia (N = 1,331,010), sleep duration (N = 446,118), napping (N = 452,633), and daytime sleepiness (N … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…These data are consistent with previous studies that have found that genetically predicted sleep traits (chronotype, daytime sleepiness, long/short sleep lengths, insomnia) were largely causally linked to an elevated risks of hypertension and heart failure 22 , 43 . Sleep traits have also been causally associated with cardiometabolic risk factors such as BMI, which may partly explain why positive associations between poor and moderate sleep qualities and BP were dramatically modulated in models further adjusted for BMI in our regression analyses 44 , 45 .…”
Section: Discussionmentioning
confidence: 95%
“…These data are consistent with previous studies that have found that genetically predicted sleep traits (chronotype, daytime sleepiness, long/short sleep lengths, insomnia) were largely causally linked to an elevated risks of hypertension and heart failure 22 , 43 . Sleep traits have also been causally associated with cardiometabolic risk factors such as BMI, which may partly explain why positive associations between poor and moderate sleep qualities and BP were dramatically modulated in models further adjusted for BMI in our regression analyses 44 , 45 .…”
Section: Discussionmentioning
confidence: 95%
“…However, it remains elusive whether the association between sleep duration and BMI is causal [60]. Sleep breathing disorders are also highly associated with obesity [61], and robust causal effects of insomnia on higher BMI have been reported in MR studies [62,63]. Regarding genetic risk, a previous study on the MGB Biobank indicated that a polygenic index for sleep duration was associated with obesity [37].…”
Section: Discussionmentioning
confidence: 99%
“…After observing that sleep duration was more closely related in young people, we conducted more detailed analyses, including subgroup and sensitivity analyses, in participants aged <45 years. For subgroup analysis, previously reported potential modifiers, such as snoring, sex [ 19 ], BMI [ 20 ], and regular physical exercise [ 21 ], were selected. Simultaneously, to clarify the joint effect of sleep quality and sleep duration trajectory, snoring and sleep duration trajectory were combined and the participants were regrouped.…”
Section: Methodsmentioning
confidence: 99%